Ciceronian ingenium and its reception in the Baroque by the Jesuists: from Ignatius of Loyola’s sensory mysticism to Baltasar Gracián’s aesthetics of wit (Minerva, 2021)
This article intends to be framed within the studies of classical reception in the modernity. It analyses how Ciceronian ingenium was received by the Jesuit thinking in the 17th century Baroque. To this end, the initial premises focus on Cicero’s ingenium in the classical period. Subsequently, the attention moves on to reveal how Cicero’s ingenium informs Ignatius of Loyola`s mystical and religious imagery and how, in turn, this influences the literary poetics of the Baroque, as exemplified in Baltasar de Gracián’s work. Baltasar Gracián gave an aesthetic sense to Cicero’s ingenium, which had only been used at an educational level until then. He then reshaped it, following his own ideas and the aesthetic canon of the Counter-Reformist Baroque. Thus, this paper presents how the premises of Cicero’s ingenium discussed at the beginning were transformed according to Gracián’s ideas and his socio-historical references.
Keywords: Cicero; ingenium; Baroque Aesthetics; Gracián